Analysis of the influence of the International Council of Nurses and the Rockefeller Foundation activity on the origin of Polish nursing - Smoleń, Ewa; Dobrowolska, Beata (Nursing in the 21st Century, 2013)
ANALYSIS OF THE INFLUENCE OF THE INTERNATIONAL COUNCIL OF NURSES AND THE ROCKEFELLER FOUNDATION ACTIVITY ON THE ORIGIN OF POLISH NURSINGThe International Council of Nurses (ICN) – is the organization that was established in 1899 as a federation of national nurses associations. ICN is free from any national and political parties’ influences. The aim of the ICN at the beginning was to help and support in process of establishing national nurses’ associations, unifying recruitment requirements for nursing candidates, regulation of the law regarding nursing education and nursing work. Activity of ICN supported exchange of experience in the specific nursing fields and highlighted the importance of principles of nursing professional ethics. Moreover, activities undertaken by ICN were aimed at improving the social status of nursing profession.The Rockefeller Foundation was established in 1913 in the USA. The foundation gave the chance to Polish nurses to get fellowships abroad. Representatives of the Foundation systematically controlled Polish centers of nursing education.Polish nursing benefited – especially in the period between two world wars – from good experience and support of ICN and the Foundation, and reached the high level of professionalism.